An International Hub in the frame of the International Walking Encounters/Conference/Walking as a Question, organized by Visual March to Prespa - (:unkn) unknown (My University, 2026)
Walking: The Cyprus Experience Cyprus Hub seminar coordinator: Dr Gabriel Koureas Cyprus Hub organized by Cut Contemporary Fine Arts Lab (Klitsa Antoniou) An International Hub in the frame of the International Walking Encounters/Conference/Walking as a Question, organized by Visual March to Prespa, Fine and Applied Arts of the School of Fine Arts of the University of Western Macedonia (EETF/UOWM), and by Made of Walking (VI). “Performing Embodied Crossings” Sunday July 4th to Sunday July 11th, 2021, Prespa, Greece Cyprus Hub Seminar Coordinator: Dr Gabriel Koureas